Postcesarean wound infection: prevalence, impact, prevention, and management challenges - Zuarez-Easton S; Zafran N; Garmi G; Salim R (Dove Medical Press, 2017)
Sivan Zuarez-Easton,1 Noah Zafran,1,2 Gali Garmi,1,2 Raed Salim1,2 1Department of Obstetrics and Gynecology, Emek Medical Center, Afula, 2Rappaport Faculty of Medicine, Technion-Israel Institute of Technology, Haifa, Israel Abstract: Surgical site infection (SSI) is one of the most common complications following cesarean section, and has an incidence of 3%–15%. It places physical and emotional burdens on the mother herself and a significant financial burden on the health care system. Moreover, SSI is associated with a maternal mortality rate of up to 3%. With the global increase in cesarean section rate, it is expected that the occurrence of SSI will increase in parallel, hence its clinical significance. Given its substantial implications, recognizing the consequences and developing strategies to diagnose, prevent, and treat SSI are essential for reducing postcesarean morbidity and mortality. Optimization of maternal comorbidities, appropriate antibiotic prophylaxis, and evidence-based surgical techniques are some of the practices proven to be effective in reducing the incidence of SSI. In this review, we describe the biological mechanism of SSI and risk factors for its occurrence and summarize recent key clinical trials investigating preoperative, intraoperative, and postoperative practices to reduce SSI incidence. It is prudent that the surgical team who perform cesarean sections be familiar with these practices and apply them as needed to minimize maternal morbidity and mortality related to SSI. Keywords: cesarean section, management, surgical site infection